Seleção de melhor desempenho de genótipos de brócolis ramoso roxo em condições tropicais - Pereira, Nara Rubia (Universidade Federal de São Carlos, 2025)
The main objective of this study was to evaluate the agronomic characteristics of purple sprouting broccoli lines (Brassica oleracea var. italica), aiming to identify materials with better adaptation to tropical conditions and potential for use in genetic breeding programs focused on developing tropicalized cultivars. The experiment was conducted at the Center for Agrarian Sciences of the Federal University of São Carlos (UFSCar) – Araras Campus, using a randomized block design with ten genotypes, plus the commercial hybrid ‘Seattle’ and the cultivar ‘Piracicaba Precoce’ as controls. The parameters evaluated included inflorescence coloration, bead size, total fresh mass, average number of inflorescences, and the length and diameter of primary and secondary inflorescences. Data were analyzed using the Scott-Knott test at 5% significance. ‘Seattle’ presented the highest yield in total fresh mass (0.675 kg\plant) and number of inflorescences (21.3), while lines 204-21 and 7101/10 demonstrated fine bead size, good purple coloration, and productive performance with statistically similar values—characteristics of great interest for the market and for crosses in hybrid production. The results highlight the potential of lines 204-21 and 7101/10 as promising materials for the development of tropicalized purple sprouting broccoli hybrids, a type of cultivar still unprecedented in the Brazilian market. Thus, the study contributes to the advancement of national genetic breeding, promoting greater diversification, sustainability, and competitiveness in horticulture in warm climate regions.
Selection for the best-performing genotypes of purple sprouting broccoli under tropical conditions
Keywords: Melhoramento genético; Brócolis ramoso; Adaptação tropical; Antocianinas; Avaliação agronômica; Genetic breeding; Sprouting broccoli; Tropical adaptation; Anthocyanins; Agronomic evaluation; CIENCIAS AGRARIAS::AGRONOMIA; 2. Fome Zero e Agricultura Sustentável